Hasil Uji Keterbacaan Modul 6M Berbasis Project Based Learning pada Peserta Didik di SMA Negeri 1 Brangrea - Hamdani Hamdani; Fitri Rahmawati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
This research aims to determine the results of the project-based learning (PjBL) 6M module readability test for students at State SMA 1 Brangrea, West Sumbawa Regency. The research method uses the ADDIE development model. The research approach uses descriptive quantitative. Data was collected using a readability test sheet instrument by class X students. The research sample consisted of 14 students from class X science at State SMA 1 Brangrea. The data from the readability test were analyzed using the mean score and validation criteria. The results of the readability test showed the average score of all aspects assessed was 68.64 with a percentage value of 71.50% included in the easy criteria. The conclusion from this study is that the 6M module based on project based learning (PjBL) for students can be applied in learning the material for environmental change in class X science in high school in West Sumbawa Regency.